Pengaruh Motifasi Kerja, Gaya Kepemimpinan dan Budaya Organisasi Terhadap Kinerja Karyawan BPR di Kabupaten Tulungagung dalam Perspektif Islam - Andayani, Dwi (INOVATIF: Jurnal Penelitian Pendidikan, Agama dan Kebudayaan, 2016)
Along with the development of word trade, the devolepment banks are increasingly rapidly. This is because the development of the banking world can not be separated from the development of trade. In Indonesia alone development of very large banks. Of the entire market share of Indonesia became Asean region with 70 percent market share potential. Indonesia Indonesia is currently appearing as kekuatan 16 of the world’s largest, with a GNP of U.S.$ 3800, Continues to grow and provide positive expeztations. With a potensial market of 180 milion people , indonesia can perch be the fourth largest economic power if it followed the stability of economic growth. But to achieve that deram must clean up the banking sector to face the competitive world of banking continues to work hard to improve professionalism. Should not be overlooked that in the end many common banking companies owned foreign banks. According to constitution of Basic Banking NO.7 of 1992 and reaffirmed by the release of constitution. No.10 of 1998 is based on the type of banking functions consist of; commercial banks and rural bank (BPR). BPR plays an important role as guardians of the nation’s economy. Entering the ASEAN Economic Community (AEC) in 2015, financial institutions that focus on small business is like a house keeper for the national economy. Entering the open market Asean, BPR has a formidable task, keeping them in groups of foreign bank entry does not size Indonesian markert. To be able to compete on the open market, it is appropriate BPR managers continue to work hard to improve professionalism. From these results of this research, writer concluded that: (1) employee motivation of BPR in Tulungagung generaly entered in both categories is 66.3% with a frequency of 53 people, (2) leadership style of BPR ingeneral Tulungagung entry in either category that is 90% with a frequency of 72 people, (3) organizational culture Tulungagung of BPR in general enterd the category of either 98% with a frequency of 79. (4) There is a positive and significant effect between work motivation, leadership styles, and organizational culture on employee performance of BPR in Tulungagung. In F counted of 8.423 with a probability value of 0.000, the calculated F (8.423)> F table (2.72), and sig is smaller than the probability value of 0.05, or a value of 0.000<0.05. Then ha is accepted, meaning together X1, X2 an X3 significant effect on Y